Dynamics of Youth Image in Sampoerna A-mild Cigarette Advertising 2020-2022 Edition - Alga Sapanca; Filosa Gita Sukmono (Jogjakarta Communication Conference (JCC), 2023)
This research aims to investigate the dynamics of youth image representation in A-Mild cigarette advertisements in three editions. By utilizing a qualitative descriptive research method and Roland Barthes' semiotic analysis as the main reference, the study seeks to understand how young people are portrayed in the scenes of the advertisement. The first advertisement portrays a series of events that are closely related to the lives of people, particularly youth in Indonesia. The second advertisement features youth as the main character, specifically addressing the issue of indiscriminate littering. The third advertisement depicts youth as powerful figures who are able to influence others to follow their actions. The findings of this study indicate that youth are perceived as agents of change, and their actions can have significant impact on society. This research is distinct from previous studies as it employs a periodization of 2020-2022, represented by one advertisement per year, to examine the representation of youth image in A-Mild cigarette advertisements across various editions.